Peran Konseling Pendeta dalam Bimbingan Rohani dan Kebiasaan Positif Bagi Pemuda Kristen - Tahith Aldrich Nanariain; Milton T. Pardosi (Harati: Jurnal Pendidikan Kristen, 2024)
In the dynamics of modern life, the challenges faced by the younger generation in maintaining a balance between spiritual aspects and the material world are increasingly complex. Social changes, environmental pressures, and the influence of technology have significantly influenced their thinking and behaviour. In this context, the role of the congregational pastor or pastor as a spiritual figure is crucial in restoring spirituality and strengthening positive habits for young people. This research uses a descriptive qualitative approach to explore young people's experiences and perceptions of congregational pastoral counselling and its impact on the formation of spirituality and positive habits. The research results show that congregational pastoral counselling not only addresses spiritual problems but also helps strengthen the foundation of their spiritual life. This research also identified patterns and themes in positive behaviour change through analysis of counselling participants' narratives. In conclusion, pastoral counselling has an important role in helping young people overcome the challenges of modern life and develop their spiritual potential.